2020
DOI: 10.1002/ptr.6965
|View full text |Cite
|
Sign up to set email alerts
|

Purpurin: A natural anthraquinone with multifaceted pharmacological activities

Abstract: Purpurin is a naturally occurring anthraquinone isolated from the roots of Rubia cordifolia. Historically, it has been used as a red dye. However, its photosensitizing property and biological effects have deciphered its novel application. Purpurin shows antigenotoxic, anticancer, neuromodulatory, and antimicrobial potential associated with antioxidant action in in vivo and in vitro experiments. A robust antioxidant nature of purpurin is responsible for the majority of its pharmacological effects. It produces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 52 publications
0
27
0
1
Order By: Relevance
“…At the same time, there is no report related to purpurin toxicity. On the contrary, in vitro, and in vivo studies have been reported that it has antioxidant, antimicrobial, anticancer, and neuroprotective effects [39]. 9-aminoacridine and hexylresorcinol, which have less binding affinity for topo IIβ than the other compounds, are also likely to cause toxicity (skin sensitization, Table 3).…”
Section: Probable and Nontoxic Human Topo Iiβ Inhibitorsmentioning
confidence: 99%
“…At the same time, there is no report related to purpurin toxicity. On the contrary, in vitro, and in vivo studies have been reported that it has antioxidant, antimicrobial, anticancer, and neuroprotective effects [39]. 9-aminoacridine and hexylresorcinol, which have less binding affinity for topo IIβ than the other compounds, are also likely to cause toxicity (skin sensitization, Table 3).…”
Section: Probable and Nontoxic Human Topo Iiβ Inhibitorsmentioning
confidence: 99%
“…Rubia cordifolia mainly includes purpurin glycosides, while Rubia tinctorum L. mainly contains alizarin glycosides. 16 Although not eaten for nutrition, the radiant roots are used as food coloring and have been used in traditional medicine to treat various ailments. 17 Purpurin appears to exhibit antiangiogenic activity, anti-fungal, anti-inflammatory, anti-tumor, anti-oxidation, and antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Mollugin (derivative of anthraquinone) inhibits pro-inflammatory chemocytokine production [12]. Purpurin is another anthraquinone that gives R. cordifolia L antioxidant properties [13]. Alizarin, 6-hydroxyrubiadin, purpurin and rubiadin are expected to be key constituents responsible for analgesic and anti-inflammatory properties [14].…”
Section: Introductionmentioning
confidence: 99%